GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Mussels enhance digestive enzyme activity in preparation for stressful fluctuating environments - Jordan A. James Bond; Petra I. Escobar; Newton Z. Hood; Helen C. Hong; Daniel R. Rankins; Grace Chan; Jade V. Betancourt; Karina Brocco French; Nichole D. Procter; Beck A. Wehrle; Kwasi M. Connor (Journal of Comparative Physiology B, 2026)
Elevated heat and low phytoplankton abundance are physiologically and ecologically challenging marine organisms of the northeast Pacific, including the mussel Mytilus californianus . During low tide, mussels are exposed to warm air and undergo anaerobic metabolism. Tidal variation coincides with daily fluctuations in food availability requiring flexible response systems (e.g., changes in digestive enzyme activity) to maintain homeostasis. In this study we allowed mussels to acclimate in tidal mesocosms with or without aerial heat across high and low levels of food abundance, after which we measured amylase (carbohydrase) activity and gene expression. Remarkably, enzyme activity was unpredictably elevated during low tide in fasted or moderate heat-stress (+ 8 °C; 23 °C) conditions, thereby potentially mitigating energy losses posed by environmental stress. Heat stress combined with fasting (multistressor) presented a marked challenge for mussels as evidenced by lower amylase activity compared to other treatments. A subsequent acute aerial heat-shock (+ 17 °C; 32 °C) negatively impacted amylase activity across all acclimation groups. Gene expression of amylase was anticorrelated with activity suggestive that mussels’ sense environmental fluctuations and respond by regulating digestive enzyme activity. Although mussels can employ these strategies to dampen short-term stress, the heatwaves predicted to persist in their ecosystems in the future may curtail their effectiveness.

Investigating the influence of edifice collapse on the geochemical and mineralogical composition of eruptives: a case study of the Poto and Paetahi tephra formations of Mt. Taranaki, New Zealand - Shannen A. Mills; Georg F. Zellmer; Anke V. Zernack; Jonathan N. Procter; Shane J. Cronin; Daniel A. Coulthard; Nessa G. D’Mello (Bulletin of Volcanology, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Clinical Observations Associated with Phenobarbital Serum Monitoring to Manage Epilepsy in a California Sea Lion with Domoic Acid Toxicosis - Claire A. Simeone; Gregory Scott; Ryan A. Navarro; Diana Procter (Oceans, 2022)
The marine algal toxin domoic acid is an important threat to marine mammal health, and exposure can lead to both acute neurologic signs and a chronic epileptic syndrome in California sea lions (Zalophus californianus). Phenobarbital has been used for several decades to manage seizures, although reports are limited correlating dosing, serum monitoring and clinical efficacy in this species. This report details serum monitoring over 33 months in an 8-year-old male sea lion. Seizure control was achieved when phenobarbital concentrations were above 18 μg/mL, and sedation and ataxia were noted when concentrations were above 35 μg/mL. There was no clinically significant difference between phenobarbital concentrations resulting from once-daily versus twice-daily dosing. Serum levels remained detectable as far as 101 days after administration, and remained stable during periods of prolonged anorexia, although dramatic decreases in serum concentrations were noted immediately after normal eating resumed. For this animal, a serum phenobarbital target range of 20–30 μg/mL was achievable with a dose of 1.5 mg/kg once daily followed by therapeutic monitoring, and this is a reasonable recommended concentration and initial dose for clinicians treating this species. Long-term seizure control may be difficult to achieve with anti-epileptic drugs such as phenobarbital alone, and further research is needed to make novel options useful for clinical management of biotoxin-related neurologic disease in this aquatic species.

Computable general equilibrium modelling of economic impacts from volcanic event scenarios at regional and national scale, Mt. Taranaki, New Zealand - G. W. McDonald; S. J. Cronin; J.-H. Kim; N. J. Smith; C. A. Murray; J. N. Procter (Bulletin of Volcanology, 2017)

Using expert judgments to inform economic evaluation of ecosystem-based adaptation decisions: watershed management for enhancing water supply for Tegucigalpa, Honduras - A. Procter; T. McDaniels; R. Vignola (Environment Systems and Decisions, 2017)

Plant community change mediates the response of foliar δ15N to CO2 enrichment in mesic grasslands - H. Wayne Polley; Justin D. Derner; Robert B. Jackson; Richard A. Gill; Andrew C. Procter; Philip A. Fay (Oecologia, 2015)

Characterization of Recombinant Human IL-15 Deamidation and Its Practical Elimination through Substitution of Asparagine 77 - David F. Nellis; Dennis F. Michiel; Man-Shiow Jiang; Dominic Esposito; Richard Davis; Hengguang Jiang; Angela Korrell; George C. Knapp; Lauren E. Lucernoni; Roy E. Nelson; Emily M. Pritt; Lauren V. Procter; et al. (Pharmaceutical Research, 2012)

A medial to distal volcaniclastic record of an andesite stratovolcano: detailed stratigraphy of the ring-plain succession of south-west Taranaki, New Zealand - A. V. Zernack; S. J. Cronin; V. E. Neall; J. N. Procter (International Journal of Earth Sciences, 2011)

Primary Productivity and Water Balance of Grassland Vegetation on Three Soils in a Continuous CO2 Gradient: Initial Results from the Lysimeter CO2 Gradient Experiment - Philip A. Fay; Alexia M. Kelley; Andrew C. Procter; Dafeng Hui; Virginia L. Jin; Robert B. Jackson; Hyrum B. Johnson; H. Wayne Polley (Ecosystems, 2009)

Imbalance of a serotonergic system in frontotemporal dementia: implication for pharmacotherapy - D. M. Bowen; A. W. Procter; D. M. A. Mann; J. S. Snowden; M. M. Esiri; D. Neary; P. T. Francis (Psychopharmacology, 2008)

Regional IUCN Red Listing: the Process as Applied to Birds in the United Kingdom - M. A. EATON; R. D. GREGORY; D. G. NOBLE; J. A. ROBINSON; J. HUGHES; D. PROCTER; A. F. BROWN; D. W. GIBBONS (Conservation Biology, 2005)
The World Conservation Union (IUCN) has developed guidelines that enable the assessment of extinction risk at a regional scale. We used these guidelines to assess the extinction risk of birds in the United Kingdom for comparison with an existing assessment of conservation status. Sixty‐four species were categorized as regionally threatened, of which 12 were critically endangered. The categorizations of the 223 species assessed agreed broadly with those from the existing U.K. system, which considers more than extinction risk, thus giving a more complete assessment of conservation status. There was, however, a tendency for the IUCN process to give higher risk status to edge‐of‐range species (some of which are relatively recent colonists considered of comparatively low conservation concern) and low status to those that have declined substantially but remain common (such as many farmland birds, the focus of considerable conservation effort in the United Kingdom). The final red list depended heavily on the subjective decisions made during the assessment process. An alternative interpretation of the guidelines could have resulted in as many as 19 or as few as 6 species being listed as critically endangered. We recommend the revision of the IUCN guidelines to reduce this subjectivity, in particular with respect to the effect of extralimital populations on the likelihood of regional extinction, and hence the potential for variation in the manner of application between regional red‐list assessors. Preventing extinction does not have to be the principal driving force behind conservation action at a regional scale if the continuance of a species is safeguarded in other regions.

A Screening Procedure for Identifying Acid-Sensitive Lakes from Catchment Characteristics - N. H. Berg; A. Gallegos; T. Dell; J. Frazier; T. Procter; J. Sickman; S. Grant; T. Blett; M. Arbaugh (Environmental Monitoring and Assessment, 2005)

The molecular genetics of growth hormone deficiency - A. M. Procter; John A. Phillips III.; David N. Cooper (Human Genetics, 1998)